Preliminary evaluation of an analog procedure to assess acceptability of intimate partner violence against women: the Partner Violence Acceptability Movie Task - Gracia, Enrique; Rodriguez, Christina M.; Lila, Marisol (Frontiers in Psychology, 2015)
Acceptability of partner violence against women is a risk factor linked to its perpetration, and to public, professionals’ and victims’ responses to this behavior. Research on the acceptability of violence in intimate partner relationships is, however, limited by reliance solely on self-reports that often provide distorted or socially desirable accounts that may misrepresent respondents’ true attitudes. This study presents data on the development and initial validation of a new analog task assessing respondents’ acceptability of physical violence toward women in intimate relationships: the Partner Violence Acceptability Movie task (PVAM). This new analog task is intended to provide a more implicit measure of the acceptability of partner violence against women. For this analog task, clips were extracted from commercially available films (90-second segments) portraying partner violence. Two independent samples were used to develop and evaluate the PVAM: a sample of 245 undergraduate students and a sample of 94 male intimate partner violence offenders. This new analog task demonstrated acceptable internal consistency. Results also indicated adequate construct validity. Both perpetrators and undergraduates scoring high in the PVAM also scored higher in self-reported justifications of partner abuse. Perpetrators of partner violence scored significantly higher in acceptability of partner violence than the undergraduate sample (both male and female students), and male students scored higher than females. These preliminary results suggest that the PVAM may be a promising tool to assess the acceptability of violence in intimate partner relationships, highlighting the need to consider alternatives to self-report to evaluate potential beliefs about partner violence.